TAFSIR NUSANTARA: Studi kritis terhadap Marah Labid Nawawi al-Bantani - Bahary, Ansor (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2015)
The interpretation is an effort to understand, to explain the intent, knowing the content of the verses of the Koran. As a result of man's work is different from the Koran, there, the interpretation occurs experiencing developments of classical, medieval to the modern period and even contemporary. Diversity both in the method (manhaj / tariqah), style (nau '), as well as approaches (Alvan) used is unavoidable in a work of interpretation. Although there are also commentaries appear in modern times but its interpretation still follows the pattern of classical and medieval period as confirmed Nawawi al-Bantani in Muqaddimah (Iqtida lil 'bi al-Salaf al-fi Tadwin' ilm) commentary. Therefore, it is no exaggeration when Tafsir Al-Munir or Angry Labid regarded as a bridge between the traditional interpretation to modern times.